2022
DOI: 10.1111/jjns.12476
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mobile applications for patients with severe mental illness: A meta‐analysis of randomized controlled trials

Abstract: Background: A systematic review and meta-analysis was conducted to evaluate the effectiveness of mobile applications used by patients diagnosed with mental disorders. Methods: An electronic literature search in five databases including PubMed, Embase, the Cochrane Library, CINAHL, and PsychInfo was conducted. The keywords used were "mental disorder," "mental illness," "mobile phone," "smartphone," "mHealth," "application," and "app". The search was restricted to randomized controlled trials (RCTs) written in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
6
2
Order By: Relevance
“…This finding highlights the potential for app-based interventions to produce positive outcomes for individuals struggling with moderate and severe depression, even without professional support. Some studies contradicted our results, which may have been due to our study limiting the depression severity to moderate and severe.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…This finding highlights the potential for app-based interventions to produce positive outcomes for individuals struggling with moderate and severe depression, even without professional support. Some studies contradicted our results, which may have been due to our study limiting the depression severity to moderate and severe.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, limited research has explored the factors influencing better treatment outcomes, with some studies yielding inconsistent findings. 20,22,27 These findings call for further investigation into the efficacy and potential factors that could enhance or attenuate the effectiveness of app-based treatments for moderate to severe depression. Therefore, this systematic review and meta-analysis aimed to examine the efficacy and associated variables of app-based interventions for depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reviews targeted specific indications, including type 2 diabetes (T2DM) ( n = 5) 19 , 20 , 22 , 23 , 26 , hypertension ( n = 4) 15 , 27 , 31 , 38 , depression ( n = 3) 33 , 53 , 61 , overweight/obesity ( n = 3) 40 , 41 , 52 , chronic obstructive pulmonary disease (COPD) ( n = 2) 35 , 39 , urinary incontinence ( n = 2) 56 , 62 , asthma ( n = 1) 57 , autism spectrum disorders ( n = 1) 32 , post-traumatic stress disorder (PTSD) ( n = 1) 59 , type 1 diabetes ( n = 1) 47 , Parkinson’s disease ( n = 1) 45 , knee arthroplasty ( n = 1) 46 and lower back pain ( n = 1) 51 . Twenty-two reviews covered multiple conditions within their scope, such as diabetes of various types ( n = 7) 18 , 21 , 24 , 25 , 36 , 37 , 50 , chronic non-communicable diseases ( n = 2) 55 , 58 , anxiety and depression ( n = 2) 43 , 49 , conditions requiring rehabilitation ( n = 2) 42 , 44 , pediatric diseases ( n = 1) 54 , diseases requiring medication ( n = 2) 17 , 34 , cardiovascular diseases ( n = 2) 16 , 30 , pain conditions ( n = 2) 48 , 60 , mental illnesses ( n = 1) 28 , or a combination of diabetes and hypertension ( n = 1) 29 .
…”
Section: Resultsmentioning
confidence: 99%
“…Two reviews additionally reported results for medication adherence 17 , 61 , one 61 on psychiatric admissions, medication adherence and side effects, resilience, attitudes, sleep disturbances and further psychological and behavioral outcomes 61 . Further reviews reported on depressive 28 , 43 , 49 , mania and psychotic symptoms as well as adverse events 28 and anxiety symptoms 43 , 49 in samples that did include depression patients, however not exclusively. Outcomes evaluated in other mental health indications included symptoms related to PTSD 59 , positive and negative psychotic symptoms including hallucinations or delusions and absence of experience (in schizophrenia), mania and depression symptoms (bipolar disorder) 28 , and autism-related outcomes based on the Mullen Scales of Early Learning, MacCarthur-Bates Communication Development Inventory and Communication and Symbolic Behavior Scales 32 .…”
Section: Resultsmentioning
confidence: 99%